In Memoriam. Ülo Kauer (25.06.1922-9.06.2004) - Sõrg, Mart (Estonian Discussions on Economic Policy, 2014)
Docent Ülo Kauer was one of the founders of finance and credit teachings at the Chair of Finance and Credit in the University of Tartu after the Faculty of Economics was moved from Tallinn back to Tartu. He took up his employment with the Chair of Finance and Credit right after the establishment of the Chair in 1957 and worked there until his retirement at the age of seventy-two in February 1994. He came to the University of Tartu from Valga Technical School, where he had worked as a teacher, and was given the position of a senior lecturer because of his teaching experience. Here he defended his dissertation and became a docent in 1969, remaining in this position for almost 25 years.The years of Ülo Kauer`s youth were shadowed by war. In July 1941 he was mobilised to the Soviet Army where he served until autumn 1944. After returning to civilian life he had to attain upper secondary education. Thereafter he enrolled as a student in the Faculty of Economics of Tallinn Polytechnic Institute that he graduated with distinction in 1950. But even before he graduated from the Institute, he was sent to Valga Technical School of Accounting and Planning to work as a teacher in autumn 1949 and after the school was closed down he was asked to become a teacher of the Chair of Finance and Credit of Tartu State University.According to his colleagues, Ülo Kauer was extremely thorough in his research as well as teaching work. This is also the reason why his teaching aids and lectures were held in high regard. He penned almost 50 teaching aids and articles on banking. Furthermore, he was one of the most acknowledged authors of the Estonian Encyclopaedia and wrote more than 120 keyword articles for the Encyclopaedia. His doctoral dissertation, which discussed financing problems in the area of construction of residential buildings in Estonia, was extremely thorough and developed into a work of 340 pages.Besides his thorough approach to work, Ülo Kauer was also very friendly and helpful, which is why he was trusted many central managerial tasks at the Faculty of Economics of the University. He was Deputy Dean of Distance Learning and Chairman of Methodology Committee for a long time. He served as Secretary of Dissertation Committee for three years and was constantly given the job of course supervisor. Moreover, he gave a large number of lectures and taught both full-time and part-time (distance learning) students.Ülo Kauer was born in Tartu to a gardener’s family. This is why he was also interested in horticulture, especially in growing roses. Hence, after he was employed by the University he started to build a house and create a garden on the bank of River Emajõgi where he could enjoy summer nights with his family, away from the noise of the town centre. His wife and daughter also chose teaching as profession. This love for education characterises the atmosphere in their family. A thorough researcher, Ülo Kauer became one of internationally recognised experts in the field of philately. He had more time to indulge in this hobby during his years of retirement. Besides his mother tongue, he knew the German, English and Russian languages and was therefore a sought-after philately consultant and expert for German philatelists.Ülo`s earthly path ended a few days before his 82th birthday. He is buried to Raadi Cemetery in Tartu where rest most of his colleagues and scientists and researchers of Tartu. We cherish the memory of Ülo as a very diligent and thorough researcher who was our role model and source of inspiration.